The Role of Cultural Values in the Interpretation of Significant Life Experiences - Ming-yeh Lee (Adult Education Research Conference, 1999)
Researchers in adult education have investigated the phenomenon of meaning-making for decades. However, majority of studies mainly focus on the psychological process of meaning-making, rather than examining how contextual elements, especially cultural values, affect the process of interpretation. The purpose of this study was to explore the role of cultural values in the interpretation of significant life experiences as perceived by Taiwanese Chinese in the U. S.